Advanced practice providers in academic emergency medicine: A national survey of chairs and program directors. (17th December 2021) - Carpenter, Christopher R.; Abrams, Stacy; Courtney, D. Mark; Dorner, Stephen C.; Dyne, Pamela; Elia, Tala; Jourdan, Daniel N.; Kaji, Amy H.; Martin, Ian B. K.; Mills, Angela M.; Nagasawa, Kat; Pillow, Malford; et al.
Abstract: Background: The Society for Academic Emergency Medicine Board of Directors convened a task force to elucidate the current state of workforce, operational, and educational issues being faced by academic medical centers related to advanced practice providers (APPs). The task force surveyed academic emergency department (ED) chairs and residency program directors (PDs). Methods: The survey was distributed to the Association of Academic Chairs of Emergency Medicine (AACEM)‐member chairs and their respective residency PDs in 2021. We surveyed 125 chairs with their self‐identified PDs. The survey sampled hiring, state‐independent practice laws, scope of practice, teaching and supervision, training opportunities, delegation of procedures between physician learners and APPs, and perceptions of the impact on resident and medical student education. Results: Of the AACEM‐member chairs identified, 73% responded and 47% of PDs responded. Most (98%) employ either physician assistants or nurse practitioners. Among responding departments, 86% report APPs working in fast‐track settings, 80% work in the main ED, and 54% work in the waiting room. In 44% of departments, APPs and residents evaluate patients concurrently, and 2% of respondents reported that APPs manage high‐acuity patients without attending involvement. Two‐thirds of chairs believe that APPs contribute positively to the quality of patient care, while 44% believe that APPs contribute to the academic environment. One‐third of PDs believe that the presence of APPs interferes with resident education. Although 75% of PDs believe that residents require training to work effectively with APPs in the ED, almost half (49%) report zero hours of training around APP supervision or collaborative skills. Conclusions: APPs are ubiquitous across academic EDs. Future research is required for academic ED leaders to balance physician and APP deployment across the academic ED within the context of patient care, resident education, institutional resources, professional development opportunities for APP staff, and standardization of APP EM training.